Distributed leader-following consensus of a class of nonlinear multi-agent systems - Shi, Y.; Yin, YanYan; Liu, C.; Liu, F. (2018)
© 2017 IEEE. This paper addresses the leader-following consensus issue for a type of nonlinear multi-agent systems with affine nonlinear term. A distributed control algorithm is constructed for each follower, and sufficient condition is obtained. The proposed control algorithm guarantees the state consensus of the multi-agent systems when the communication network among followers is an undirected and connected graph, and the leader sends its information to at least one follower. The effectiveness and usefulness of the theoretical results are illustrated by numerical simulation finally.